Buhay bahaghari : the Filipino LGBT chronicles - Callueng, Eva (Diliman, Philippines : University of the Philippines, Center for Women's Studies, 2014)
The Foreword to this collection argues that the general consensus about the historiographic work of the local lesbian, gay, bisexual and transgender (LGBT) literature in the Philippines is that its production is mainly from gay studies scholars. Buhay Bahaghari interrupts this. It is an edited collection of personal essays largely by lesbian, bisexual and transgender authors. In the Introduction, Eva Callueng describes her collection as similar to the Pinoy LGBT channel of the Philippine Online Chronicles" and "the first of its kind."
1. Identities and struggles -- 2. Tensions, Anxieties, Relations -- 3. Love and Lessons -- 4. Challenges, changes in our community.
Includes index.
Keywords: SEXUAL MINORITIES -- PHILIPPINES